Analisis Vegetasi Gulma Dominan Pada Pertanaman Durian (Durio zibethinus. Murr) Di Rumahkay Kabupaten Seram Bagian Barat - Vilma Laurien Tanasale; Nureny Goo; Christian W. Patty (Fakultas Pertanian, Universitas Pattimura Ambon, Indonesia, 2026)
Durian (Durio zibethinus Murr.) is a tropical fruit that is highly favored by the Indonesian community and is widely cultivated in various regions, including Rumahkay Village, West Seram Regency. However, durian production in this area has shown a declining trend over recent years. One of the factors contributing to this decline is the presence of weeds, which significantly interfere with the growth and productivity of durian plants. This study aimed to identify the weed species composition forming the vegetation and to determine the dominant weed species in durian plantations in Rumahkay Village. The research was conducted using a vegetation survey method with sample plots measuring 1 m × 1 m established beneath six durian trees. The results revealed that 31 weed species were distributed throughout the durian plantation area. The dominant weed species in Rumahkay Village, based on the highest Summed Dominance Ratio (SDR), was Oplismenus compositus with an SDR value of 17.85%.